Complexity measures and uncertainty relations of the high-dimensional harmonic and hydrogenic systems. (14th August 2017) - Sobrino-Coll, N; Puertas-Centeno, D; Toranzo, I V; Dehesa, J S
Abstract: In this work we find that not only the Heisenberg-like uncertainty products and the Rényi-entropy-based uncertainty sum have the same first-order values for all the quantum states of the D -dimensional hydrogenic and oscillator-like systems, respectively, in the pseudoclassical ( D → ∞ ) limit but a similar phenomenon also happens for both the Fisher-information-based uncertainty product and the Shannon-entropy-based uncertainty sum, as well as for the Crámer–Rao and Fisher–Shannon complexities. Moreover, we show that the López–Ruiz–Mancini–Calvet (LMC) and LMC-Rényi complexity measures capture the hydrogenic-harmonic difference in the high dimensional limit already at first order.